AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRICS OF NADIN AMIZAH - Liens Mariyanti Gowasa; Opirman Waruwu (Universitas Nias Raya, 2025)
This study aims to identify and analyze the types of figurative language found in four song lyrics by Nadin Amizah, namely